Analisis Kadar Vitamin C Kelopak Rosella (Hibiscus sabdariffa L.) Muda dan Tua yang dikoleksi Dari Berbagai Ketinggian Tempat yang Berbeda - Heni Setyawati; M. Ali Mustofa (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
The aims of the research was to know the vitamin C content in unripe and ripe rosella calyx in three different altitudes. Rosella calyx which were used in this research were taken from three different altitudes. There were Glagah beach (7 masl), KP4 Berbah (126 masl), and Samigaluh (600 masl). The vitamin C content were determined by titration method using 2,6-dichlorophenolindophenol. The result of this research showed that vitamin C content in unripe rosella calyx was not significantly different. The highest vitamin C content in ripe rosella calyx at 7m and 600m altitude were not significantly different. And the vitamin C content in unripe and ripe rosella calyx at 7 masl and 600 masl were also not significantly different. Vitamin C content in unripe rosella calyx at 126 masl was 2,269 mg/g, higher than the ripe (1,316 mg/g). It could be concluded that the altitude and the age of calyx influence vitamin C content in rosella calyx.